Projected climate change threatens pollinators and crop production in Brazil - Giannini, Tereza C. (2017)
Fil: Giannini, Tereza C. Instituto Tecnológico Vale Desenvolvimento Sustentável; Brasil. Universidade de Sao Paulo; Brasil